The role of mDia1 during the initiation of polarization and migration of chick embryo cardiac fibroblasts - Tahtamouni, Lubna, author; Mykles, Donald L., advisor; Bamburg, James R., advisor; Bedinger, Patricia A., committee member; Reist, Noreen E., committee member; Reddy, A. S. N., committee member (Colorado State University. Libraries, 2005)
During directional migration, cells exhibit a polarized morphology with leading edge protrusion and retraction at the rear. Polarization requires coordinated reorganization of actin and microtubules. mDia1, a member of the formin family of proteins, coordinates both actin and microtubule cytoskeletons through its FH1-FH2 unit. We hypothesized that both constitutively active (CA) and dominant negative (DN)mDia1 will disrupt the polarization and thus the migration of chick embryo cardiac fibroblasts (CECF) through their effects on actin and microtubules. We used adenoviral mediated gene expression coupled with GFP and RFP expression for 24 h prior to plating the explants or 48 h prior to plating dissociated cells. Our results indicate that 24.9%and 4.8% of cells expressing CAmDia1 or DNmDia1, respectively, exhibited polarized morphology (protrusion of a single lamellipodium) compared to 52% in uninfected and control adenovirus-infected cells. Cell migration in culture was followed by time-lapse microscopy. Polar and bipolar cells infected with CA-mDia1 adenovirus retained the capacity to migrate, but they were slower (0.49 μm/min and 0.11 μm/min, respectively) than their control-infected counterparts (1.14 μm/min and 0.34 μm/min, respectively). Overexpression of CAmDia1 increased the size (41.8%, and 159 .6% increase for polar and bipolar CECFs, respectively), number (53.1 % increase for polar CECFs), and total area (112.7%, and 61.9% increase for polar and bipolar CECFs, respectively) of focal adhesions in CECFs, and increased the formation of stabilized microtubules (Glumicrotubules), but had no effect on G-actin/F-actin balance in these cells. Together, our data demonstrate that mDia1 regulates cell adhesion and microtubule dynamics in CECFs, both of which are critical for cell migration. More than 60% of CAmDia1infected dissociated CECFs had circumferential F-actin phenotype after 1 h of plating, compared to 23% in control uninfected and GFP-infected dissociated CECFs. CAmDia1expressing dissociated CECFs that were blocked at the circumferential stage had a higher phosphoAC/cofilin ratio than the control uninfected cells. Furthermore, when CECFs expressing CAmDia1 were co-infected with adenovirus expressing an active nonphospho-regulated ADF/cofilin, cells progressed to the next stage of polarization, the F-actin oriented phenotype. Thus, CAmDia1 overexpression in dissociated CECFs results in the block of progression from the circumferential to the oriented stage by inactivating ADF /cofilin. Cells infected with DN-mDia1 failed to migrate out of the explants, and DNmDia1-infected dissociated CECFs failed to adhere. Thus it was impossible to obtain data on focal adhesions size and number. However, co-infection of DNmDia1-expressing CECFs with adenovirus expressing wild-type paxillin (a focal adhesion protein), rescued the ability of the cells to migrate out of the explants, suggesting that the migration defects of these cells results from faulty adhesion. The CAmDia1-mediated enhanced microtubule stabilization minimized the ability of microtubules to target focal adhesion leading to their disassembly, which in turn caused loss of polarization and reduction in migration rate of CECFs. On the other hand, the absence of mDia1 resulted in faulty adhesion and migration defects.
Keywords: molecular biology; zoology; cellular biology; anatomy and physiology; animals